Toward a contextual theological reading of John Amos Comenius - Glenn, Justin (International journal of Christianity & education, 2016)
John Amos Comenius developed a revolutionary philosophy of education in seventeenth-century Europe. He argued for ideas such as universal education, which was virtually unheard of in his time but has become standard in modern western society. In the middle of the twentieth century, Comenius's ideas were heralded in the secular educational community. Jean Piaget and Vladimir Jelinek are prime examples of those who promoted the conclusions of Comenius's educational philosophy while ignoring, and even refuting, his theological presuppositions. Comenius's educational philosophy, however, was built specifically on his theological beliefs, and reading him holistically has resulted in more accurate interpretations.